A multi-institutional randomized phase III study comparing weekly carboplatin plus nab-paclitaxel and daily low-dose carboplatin as regimens for concurrent chemoradiotherapy in elderly patients with unresectable locally advanced non-small cell lung cancer: Japan Clinical Oncology Group Study JCOG1914. (17th March 2021) - Shimoyama, Ryo; Omori, Shota; Nomura, Shogo; Kenmotsu, Hirotsugu; Takahashi, Toshiaki; Harada, Hideyuki; Ishikura, Satoshi; Mizutani, Tomonori; Ando, Masahiko; Kataoka, Tomoko; Fukuda, Haruhiko; Ohe, Yuichiro; et al.
Abstract: Daily low-dose carboplatin plus concurrent thoracic radiotherapy is the standard treatment for elderly patients with unresectable clinical stage (c-Stage) III non-small cell lung cancer (NSCLC) in Japan. However, a phase I study by Omori et al. suggests that weekly carboplatin and nab-paclitaxel plus concurrent thoracic radiotherapy have comparable efficacy outcomes with more manageable adverse events. In December 2020, we initiated a randomized controlled trial in Japan to confirm whether the weekly carboplatin plus nab-paclitaxel regimen is noninferior to the daily low-dose carboplatin regimen for concurrent chemoradiotherapy in elderly patients with unresectable c-Stage III NSCLC. We plan to enroll 166 patients from 50 institutions in 3.5 years. The primary endpoint is overall survival. The secondary endpoints are progression-free survival, response rate, proportion of patients starting maintenance durvalumab therapy, adverse events, site of progression, Functional Assessment of Cancer Therapy–Trial Outcome Index deterioration and Instrumental Activities of Daily Living deterioration. Abstract : A randomized controlled phase III trial has been initiated to confirm whether the weekly carboplatin plus nab-paclitaxel regimen is noninferior to the daily low-dose carboplatin regimen for concurrent chemoradiotherapy in elderly patients with unresectable locally advanced non-small cell lung cancer.